A Practical Implementation Fire Monitoring Systems Using Fuzzy Methods - Dea Ummul Khabibah; Kenzi Dewandaru; Muhammad Tsabit; Silva Dimas Surya Permana; Yana Nurrohman; Agung Prayudha Hidayat; Dwi Yulinar Chairunisa (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
Fires are serious disasters that require effective monitoring or control systems to identify risks and respond quickly. In this study, observations were made on the A Practical Implementation Fire Monitoring Systems Using Fuzzy Methods using temperature input from DHT22 sensors, smoke from MQ-2 sensors, and fire history as evaluation variables. The system will classify the temperature as "low", "medium", or "high", smoke as "low", "medium", "concentrated", as well as the history of fires categorized as "low", "medium", "high". The input will be processed using fuzzy logic to generate recommended actions, the actions are classified into "evacuate", "stay away from the area", or "wait for instructions". The implementation of the monitoring system uses the Arduino UNO platform as its base, then the DHT22 temperature sensor, and the MQ-2 smoke sensor to detect fire conditions. Then the test results from the monitoring system will provide recommendations related to more accurate and responsive actions based on actual conditions at the fire site.